Bacterial contamination of cell phones of medical students at King Abdulaziz University, Jeddah, Saudi Arabia. Issue 3 (September 2016) - Zakai, Shadi; Mashat, Abdullah; Abumohssin, Abdulmalik; Samarkandi, Ahmad; Almaghrabi, Basim; Barradah, Hesham; Jiman-Fatani, Asif
Abstract: Cell phones are commonly used in healthcare settings for rapid communication within hospitals. Concerns have been increased about the use of these devices in hospitals, as they can be used everywhere, even in toilets. Therefore, they can be vehicles for transmitting pathogens to patients. This study aimed to examine the presence of pathogenic bacteria on the surfaces of cell phones that are used frequently by preclinical medical students. This cross-sectional study identified both pathogenic and nonpathogenic bacteria on cell phones of 105 medical students at King Abdulaziz University, Jeddah, Saudi Arabia, using standard microbiological methods. Out of 105 cell phones screened, 101 (96.2%) were contaminated with bacteria. Coagulase-negative staphylococci were the most abundant isolates (68%). Seventeen (16.2%) cell phones were found to harbor Staphylococcus aureus . Gram-positive bacilli were isolated from 20 (19%) samples. Viridans streptococci and Pantoea species were also isolated but at lower levels. Our findings indicate that cell phones can act as reservoirs of both pathogenic and nonpathogenic organisms. Therefore, full guidelines about restricting the use of cell phones in clinical environments, hand hygiene, and frequent decontamination of mobile devices are recommended at an early stage in medical schools, to limit the risk of cross-contamination and healthcare-associated infections caused by cell phones.